ANTI-INFLAMMATORY GERANYL ESTER OF IBUPROFEN AND CORRESPONDING FURFURYL AND ISOAMYL AMIDES WITH IN SILICO ANALYSIS - Bepary, Sukumar; Biswas, Bishyajit Kumar; Jahan, Sayeda; Rahman, Sanjida; Islam, Md. Toufiqul (Tanjungpura University, 2024)
Ibuprofen is a commercially available and widely used non-steroidal antiinflammatory drug being used in managing inflammatory disorders worldwide. This acid molecule has been subjected to esterification by coupling with geraniol as well as to amide formation by coupling with furfurylamine and isoamylamine for observing the changes in anti-inflammatory potential due to the addition of relatively long aliphatic chains. During these reactions, the reaction yields were within 88-94%. In this in vitro evaluation, the prevention of egg albumin denaturation and human red blood cell (HRBC) membrane stabilization were observed. For observing potential for preventing egg albumin denaturation, the synthesized compounds were applied as doses of 10 Î¼g/ml, 20 Î¼g/ml, 30 Î¼g/ml, and 40 Î¼g/ml. For observing the better response from ester derivative, 50 Î¼g/ml, 100 Î¼g/ml and 200 Î¼g/ml doses were also tried. For observing the Human RBC membrane stabilization with amides, 50 Î¼g/ml and 100 Î¼g/ml doses were tried. Ibuprofen was taken as the reference compound and was applied in same doses in all of the experiments. The antiinflammatory potential of the synthesized geranyl ester was remarkable in comparatively higher doses (16%, 45%, and 54% reduction in protein denaturation from 50 Î¼g/ml, 100 Î¼g/ml, and 200 Î¼g/ml doses respectively). Isoamylamide was relatively more potent than geranyl ester in preventing egg albumin denaturation (reductions were 9%, 13%, 17%, and 31% from 10, 20, 30, and 40 µg/ml doses respectively). Furfurylamide was more potent than isoamylamide by showing 9%, 17%, 31%, and 46% inhibitions respectively. There were dose-dependent antiinflammatory actions observed from both the geranyl ester and amides. The synthesized compounds were also subjected to the in silico study for observing the ligand-receptor interactions in the binding site of the cyclooxygenase enzyme.